ANALISIS STRUKTUR PERILAKU KINERJA USAHA PERCETAKAN (STUDI KASUS PADA USAHA PERCETAKAN DI KECAMATAN SUKAJADI KOTA PEKANBARU) - Ramadhani Asmelia; Iyan Yani Rita; Aqualdo Nobel (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research was conducted in the printing business in Sukajadi District, Pekanbaru City. This research aims to find out how the structure, behavior, market performance formed in the printing business in Sukajadi District. The population in this study was 71 business units and the determination of samples using probability sampling techniques with the sample method used was the sampling design area, so that the number of samples in this study amounted to 18 units of printing business. This research method is descriptive qualitative. The data used is primary and secondary data. Primary data was obtained from 18 businesses through questionnaires and interviews. Secondary data is obtained through literature books, arikel, government agencies related to the concepts and problems studied. The data analysis tool used in this research is Structure–Conduct Performance (SCP) analysis method. Where the market structure can be seen from market share, concentration ratio of the four largest companies (CR4), HarfindahlHirschman Index (IHH), and Minimum Efficiency of Scale (MES), market behavior can be seen from Capital to Labour Ratio (CLR) and performance identified through Price Cost Margin (PCM). The results showed that the printing business structure in Sukajadi subdistrict is loose oligopoly with an average concentration ratio of the four largest companies (CR4) of 57.92% and IHH of 1101.13. Barriers to business entry are low so that new entrants have the opportunity to gain market share, known from the MES average of 7.56%. Business behavior seen from clr research results ranging from 1.44 - 6.67 this means business behavior has a tendency as a capital intensive business. The performance of the printing business with the highest PCM value of 64.2% is not the largest market share (MS). This means that the profits seen from PCM are not influenced by market share.Keywords: Structure-Behavior-Performance, Market Share, Concentration Ratio (CR4), Harfindahl-Hirschman Index (IHH), Minimum Efficiency of scal (MES), Capital to Labour Ratio (CLR), Price Cost Margin (PCM).